2008 2nd International Conference on Bioinformatics and Biomedical Engineering 2008
DOI: 10.1109/icbbe.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of NO-Char Reaction at Temperatures of 1073-1573K

Abstract: Two Chinese coals (YB lignite coal and SH bituminous coal) were used to prepare the chars. The chars were obtained in an entrained flow reactor which can simulate the temperature and gas composition of a true pulverized coal combustion environment. The kinetic characterization of NOchar reaction was performed by isothermal thermogravimetry in the temperature range 1073-1573K. It was confirmed that the reactions were under chemical kinetic control in the lowtemperature regime (1073-1273K) for SH char. The discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the last years, tandem mass spectrometry (MS/MS) has emerged as a very interesting approach since it allows minimizing matrix interferences and chemical noise in the chromatograms, improving selectivity and sensitivity. Numerous applications based on GC-MS/MS have been reported for the determination of multiclass pesticides using triple quadrupole (Cervera et al 2010;Frenich et al 2005;Medina et al 2009) or ion trap detector analyzers (González-Rodríguez et al 2008;Zhang et al 2008), some of them including around or more than 100 target analytes. In parallel to the interest of increasing the number of compounds in a single chromatographic run, there is a trend to decrease chromatographic run times in multiresidue analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, tandem mass spectrometry (MS/MS) has emerged as a very interesting approach since it allows minimizing matrix interferences and chemical noise in the chromatograms, improving selectivity and sensitivity. Numerous applications based on GC-MS/MS have been reported for the determination of multiclass pesticides using triple quadrupole (Cervera et al 2010;Frenich et al 2005;Medina et al 2009) or ion trap detector analyzers (González-Rodríguez et al 2008;Zhang et al 2008), some of them including around or more than 100 target analytes. In parallel to the interest of increasing the number of compounds in a single chromatographic run, there is a trend to decrease chromatographic run times in multiresidue analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies [8][9][10] have shown that coal char has a reduction effect on NOx during coal combustion. Zhang et al [11] illustrated the char-NO reaction in the range of 1073~1573 K by isothermal thermogravimetry using coal char obtained from an entrained-flow reactor, and found that chemical kinetics controlled the NO-char reaction at 1073~1273 K. Sun et al [12] thermodynamically characterized the char-NO reaction in the range of 973~1573 K with isothermal thermogravimetry, and found a similar phenomenon: chemical kinetics controlled the char-NO reaction at low temperature, and diffusion kinetics controlled the reaction at high temperature.…”
Section: Introductionmentioning
confidence: 99%